Sosialisasi Penggunaan Aplikasi Klasifikasi Sampah - I Made Bayu Suarjaya; Paniran (Universitas Mataram, 2024)
Waste classification application using Convolutional Neural Network (CNN) to overcome the problem of waste accumulation in Indonesia. The application socialisation was conducted in Pemangkalan Village, West Lombok, with the aim of facilitating community waste management. The results showed an increase in community understanding of the importance of waste management and active participation in protecting the environment. Periodic evaluation is needed to maintain the sustainability of the socialisation programme. Strategic steps include socialisation, development of organic waste classification methods, digital image processing technology, artificial intelligence, and cooperation between the government, educational institutions, and communities in the implementation of waste classification technology.